EVALUATION OF THE ARABIC LANGUAGE TEXTBOOK FOR GRADE 7 BY THE MINISTRY OF RELIGIOUS AFFAIRS (KEMENAG) 2020 - Rasiyani, Alfiyah; Zarkasyi, Ahmad Hidayatullah; Ummi, Rizky; Gustia, Irma (Universitas Islam Negeri Sumatera Utara Medan, 2023)
Given the importance of textbooks that meet students' needs, this study aims to analyze the strengths and weaknesses of the Grade 7 Arabic language textbook published by Kemenag in 2020. This textbook is designed to help students learn Arabic as a foreign language. The study employs a qualitative descriptive method using content analysis techniques, with data extracted directly from the textbook and analyzed based on predetermined criteria. The findings indicate that the textbook has strengths in its simplicity of language, theme relevance, and support for speaking and listening skills. However, it also has weaknesses, such as an excessive amount of vocabulary, insufficient emphasis on grammar, too many exercises, limited variety in learning media, and a lack of guidance for teachers on how to use the book effectively. This study is expected to contribute to improving the quality of Arabic language education in schools, particularly by aligning the content with the needs of non-native Arabic-speaking students